Effect of Injection of Hatching Eggs in Different Concentrations of Nano Silver at Age 17.5 Days of Embryonic Age in Some Histological Traits of Broiler Ross 308 (Medico Legal Update, 2021)
This study was conducted in the hatchery belonging to Al-Anwar Poultry Company,by injecting the hatchingeggs at the age of 17.5 days from the age of the embryos with nano Silver, after that, and raised hatchingchicks from the injected eggs in the field of poultry belonging to the Department of Animal Production,College of Agriculture, University of Al-Qasim Green for the period from 6/8/2017 until 9/9/2017, and afterthat the laboratory work was done, as it used 168 broiler chickens and was reared in cages 1 x 1.5 m, thechicks were randomly divided into seven treatments, and each treatment had three replicates, including eachreplicate of 8 chicks. Nano-silver was used by injecting it into the eggs in concentrations(0,4,6,8,10,12,14ppm) for treatments (T1,T2,T3,T4,T5,T6,T7) respectively, The chicks were raised in the field for a periodof 35 days, and in this study we reached the following results, a significant excelled (P